"In patient" medical abortion versus surgical abortion: patient's satisfaction. (2nd August 2016) - Di Carlo, Costantino; Savoia, Fabiana; Ferrara, Cinzia; Sglavo, Gabriella; Tommaselli, Giovanni Antonio; Giampaolino, Pierluigi; Cagnacci, Angelo; Nappi, Carmine
Abstract: Objective : To compare patients' satisfaction with medical and surgical abortion, implementing the Italian guidelines on medical abortion entailing an "in patient" procedure. Methods : A total of 1832 pregnant chose between surgical (vacuum aspiration) or medical abortion (mifepristone p.o. followed after 3 days by sublingual misoprostol) and expressed their expected satisfaction on a visual analog scale (VAS). A total of 885 women chose surgical and 947 medical abortion. The primary end-point was satisfaction VAS score 20 days after the procedure. Secondary end-points were: difference between pre- and post-abortion VAS score; difference in satisfaction VAS scores according to parity and previous abortion; incidence of side effects. Results : VAS score was high in each group but significantly higher for the 1-day surgical than for the 3-day medical abortion procedure (7.9 ± 1.0 versus 7.2 ± 1.2; p < 0.0001). In the surgical group the VAS score increased after the treatment (6.9 ± 1.6 versus 7.9 ± 1.0, p < 0.0001), while it decreased in the medical group (7.5 ± 1.0 versus 7.2 ± 1.2; p < 0.0001). Multiparous women reported higher satisfaction with medical abortion; women with a previous abortion preferred surgical abortion. Conclusions : Both procedures are considered satisfactory by the patients. Performing medical abortion as a 3-day "in patient" procedure, decreased women's satisfaction scores from their baseline expectations.